Implementation of clinical guidelines in specialized palliative care—results from a national improvement project: A national register-based study. (May 2023) - Rojas-Concha, Leslye; Hansen, Maiken Bang; Adsersen, Mathilde; Petersen, Morten Aagaard; Groenvold, Mogens
Background: Knowledge about the process and the results of the implementation of clinical guidelines to improve palliative care is limited. A national project aimed at improving the quality of life of advanced cancer patients admitted to specialized palliative care services in Denmark by implementing clinical guidelines for the treatment of pain, dyspnea, constipation, and depression. Aim: To investigate the degree of clinical guideline implementation by evaluating the proportion of patients treated according to guidelines among those who qualified (i.e. reported severe symptom level) before and after the 44 palliative care services implemented the guidelines, and how often different types of interventions were provided. Design: This is a national register-based study. Setting/participants: Data from the improvement project were stored in and later obtained from the Danish Palliative Care Database. Adult patients with advanced cancer admitted to palliative care between September 2017 and June 2019 who answered the EORTC QLQ-C15-PAL questionnaire were included. Results: In total 11, 330 patients answered the EORTC QLQ-C15-PAL. The proportions of services that implemented the four guidelines ranged 73%–93%. Among services that had implemented guidelines, the proportion of patients receiving interventions was roughly constant over time reaching between 54% and 86% (lowest for depression). Pain and constipation were frequently treated pharmacologically (66%–72%), whereas dyspnea and depression were frequently treated non-pharmacologically (61% each). Conclusions: Implementing clinical guidelines was more successful for physical symptoms than for depression. The project generated national data on interventions provided when guidelines were followed, which may be used to understand differences in care and outcomes.